2015
DOI: 10.1016/j.ijscr.2014.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Peritonectomy and hyperthermic intraperitoneal chemotherapy as treatment for desmoplastic small round cell tumour

Abstract: IntroductionThe St George Hospital specialises in peritonectomy and hyperthermic intraperitoneal chemotherapy (HIPEC) for treatment of intra-abdominal malignancies. Despite performing around 800 peritonectomy and HIPEC procedures, we have rarely encountered desmoplastic small round cell tumours (DSRCT). We present our experiences with DSRCT, and propose peritonectomy and HIPEC as a treatment option for DSRCT.Presentation of caseThis is a case series of 3 cases. The first case was a 26-year-old male who present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Forty-three patients with DSRCT who received intraperitoneal chemotherapy have been reported in the literature, including our 11 patients, and all after 2010 [ 15 , 20 24 ]. The only randomized controlled trial in patients with peritoneal metastases originating from sarcomas concluded that intraperitoneal chemotherapy (without hyperthermia) did not bring any survival benefit [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Forty-three patients with DSRCT who received intraperitoneal chemotherapy have been reported in the literature, including our 11 patients, and all after 2010 [ 15 , 20 24 ]. The only randomized controlled trial in patients with peritoneal metastases originating from sarcomas concluded that intraperitoneal chemotherapy (without hyperthermia) did not bring any survival benefit [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rarity of the pathology means there are currently no evidence-based therapeutic guidelines on post-resection management, although several small series have shown partial response to adjuvant chemotherapy (P6 Protocol) [ 4 , 5 , 8 ]. In select cases, cytoreductive surgery (CRS) and intraperitoneal hyperthermic chemoperfusion (HIPEC) has been provided; one case had recurrence at 8.85 months [ 11 ] while a small phase 2 trial showed overall survival of 44.3 months [ 10 ]. It should be noted the patients who underwent CRS + HIPEC were young, otherwise healthy males, while our patient is a late middle-age female and morbidly obese with numerous comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, Hirano et al [8] also published data using isolated irinotecan as second-line treatment for patients with EFS and OS of 6 and 20 months, respectively. The following year, Fan et al [4]. again tested the combination of temozolomide with irinotecan as a second-line treatment for two patients, resulting in EFS of 6 and 15 months.…”
Section: Discussionmentioning
confidence: 99%
“…A desmoplastic small round cell tumor (DSRCT) is an extremely rare and highly aggressive cancer that affects adolescents and young adults. The tumor usually begins and spreads over the surface of the peritoneum [4, 12, 15, 16].…”
Section: Introductionmentioning
confidence: 99%